Analyses of stability and support design for a diversion tunnel at the Kapikaya dam site, Turkey - Gurocak, Zulfu (Springer Heidelberg, 2011)
This paper presents the engineering geological properties and support design for a diversion tunnel through diabase at the Kapikaya dam site, eastern Turkey. The rock mass rating and rock mass index were used to determine the support requirements, which were also analyzed using commercial software based on the finite element method. The parameters calculated by the empirical methods were used as input parameters for the FEM analysis and the results from the two methods were compared. It was found that the optimum solution was obtained by using a combination of both empirical and numerical approaches.
Keywords: Finite element method; Hoek-Brown failure criterion; Kapikaya dam; RMR; RMi